Lanthanum-doped Bi4Ti3O12 prepared by the soft chemical method: Rietveld analysis and piezoelectric properties - Simões, Alexandre Zirpoli [UNESP]; Stojanovic, B. D. [UNESP]; Ramirez, M. A. [UNESP]; Cavalheiro, A. A. [UNESP]; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Elsevier B.V., 2008)
Bi4-xLaxTi3O12 (BLT) thin films and powders with x ranging from 0 to 0.75 were prepared by the polymeric precursor solution. The effect of lanthanum on the structure of BIT powders was investigated by Rietveld Method. The increase of lanthanum content does not lead to any secondary phases. Orthorhombicity of the bismuth titanate (BIT) crystal lattice decreased with the increase of lanthanum content due the reduction of a/b ratio. The BLT films show piezoelectric coefficients of 45, 19, 16 and 10 pm/V for x = 0, 0.25, 0.50 and 0.75, respectively. The piezoelectric response is strongly reduced by the amount of lanthanum added to the system. (c) 2006 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: sintering; ceramics; crystal structure